PHYTOCHEMICAL SCREENING OF MALLOTUS PHILIPINESIS FOR ITS ANTIBACTERIAL ACTIVITY - Patani M.N (Journal of Global Pharma Technology, 2011)
Mallotus philippinensis Muell. Arg. belongs to the family Euphorbiaceae is also known as kamala powder which was extracte with methanol and ethyl acetate. Present study shows that both the extracts of kamala powder have good antibacterial activity, but when compared to Gram negative bacteria, Gram positive bacteria are more susceptible to the extracts. The mechanism of antibacterial action appears to be loss of control over cell membrane permeability. Keywords: Mallotus philippinensis, Antibacterial activity, Methanol, Ethylacetate.